Faktor-Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi: Keterlibatan Pengguna, Dukungan Top Manajemen Dan Formalisasi Pengembangan Sistem - Neyla Safitri; Cris Kuntadi; Rachmat Pramukty (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to examine the effect of user involvement, top management support and system development formalization on the performance of accounting information systems. This research is a qualitative research where the type of qualitative research used in this study uses the method of literature study and literature review (literature review). The results of this study are: 1) User involvement affects the performance of accounting information systems; 2) Top Management Support affects the Performance of Accounting Information Systems; and 3) System Development Formalization affects the Performance of Accounting Information Systems